Lataif Perspektif Tafsir Sufi Najm al-Din al-Kubra - Ulum, Fahmi Raudhatul (Al-Fath, 2020)
Humans are created so perfectly, both given reason and lust, the war against lust applies to all mankind in the world, in this war the enemy is invisible to the eye, the enemy is very delicate, lat}a>’if as a means to fight the passions that must be processed as little as possible The results of this thesis are as follows: Shaykh Najmuddin Kubra in muqodimah said "Lat}a>’if is a hidden secret sign, and revealed from kalam, by revealing favors, lust and explanations for their hearts, their souls and they understand secrets, and knowledge of true science. The division 7 lat} a> if as follows: a). lat}i>fah qolabiah. b). lat}i>fah nafsiyah. c). lat}i>fah qolbyah. d). lat}i>fah sirriah. e). lat}i>fah ruhiyyah. f). lat}i>fah khafiyah. g). lat}i>fah h}aqiyah. In Surah T{a>ha> [20]: 7, Surah Al-Imran [3]: 67, Surah An-Nisa [4]: 43, Surah Al-Maidah [5]: 73, Surah Al-An'am [6]: 52 , these verses become the details in the discussion of this paper.